Olfaction-based learned preference assessment without the use of motivational fear or motivational weight loss - Moss, Sara E.; McCurdy, Ekaterina S.; Thomas, Natalya N.; Gulick, Danielle; Poff, Angela M.; D'Agostino, Dominic P. (Frontiers in Behavioral Neuroscience, 2025)
IntroductionReliable assessments of learning ability in preclinical models are essential for studying neurodegenerative, developmental, and inflammatory disorders. However, many inbred strains of mice present background pathologies that interfere with traditional learning tests. The C57BL/6 J mouse, a widely used laboratory strain, sporadically develops auditory and visual impairments that complicate interpretation. In this study, we establish an olfaction-based learned preference protocol designed to evaluate learning ability independent of fear responses, motivational weight loss, or visual cues in C57BL/6 J mice.Methods and resultsLeveraging the species’ natural preference for sweet flavors, we tested different sweeteners and confirmed their passive preference for sucrose was more robust than for saccharin or sucralose. We then trained mice to associate either lemon or rose scents with a sucrose paste reward, and tested whether they demonstrated a learned preference for the sucrose-associated scent over the neutral scent. Mice developed an appetitive olfactory preference for sucrose as a reward, in the absence of motivational weight loss, as measured by time spent exploring a three-chamber association box with access to both scents. We assessed whether this protocol discriminated learning deficit induced by lipopolysaccharide (LPS) administration.ConclusionWe conclude that this protocol is a viable tool for assessing learning abilities in preclinical models with auditory or visual deficits, motor impairments, or an inability to tolerate motivational weight loss.